Osprey observed when drowned by its prey - Husby, Magne (Ornis Norvegica, 2020)
An Osprey Pandion haliaetus was observed by eight people as it was dragged under water by a fish and drowned. Several unsuccessful attempts to leave the water surface caused the Osprey gradually to sink in the water until it disappeared. The area was searched by boat, but the fish and Osprey were gone, and it was confirmed that there were no fishing nets in the area. This is a rare event, and sometimes rejected by scientists. The good view by eight persons, and detailed descriptions I received from two independent observers make the observation credible. The Osprey was an adult bird. In addition to traditional explanations that claws can become fastened to scales, bones or flesh of the fish, I propose that muscle spasm may be a reason why the osprey was not able to release its grip. Cover illustration: Fishing Osprey. Photo: Jørn Bøhmer Olsen.